Overuse injury treatment: which is more appropriate between Swedish massage and deep tissue massage, especially for archery athletes - Prasetyo, Yudik; Yachsie, Betrix Teofa Perkasa Wibafied Billy; Suhasto, Siis; Famelia, Putri (Zdorov'i︠a︡, sport, reabilitat︠s︡ii︠a, 2025)
Purpose To determine the influence of Swedish massage and deep tissue massage on the healing of the dominant muscles in archery players. Although the impact of massage cannot be completely isolated from injury, massage frequently reduces an athlete's performance. Materials and Methods A quantitative experiment with a two-group pretest-posttest design is used in this sort of study. There were 20 participants in the purposive sampling, all male archery athletes between the ages of 15 and 20. The activity took place over the course of four meetings, with groups being separated by ordinal pairing. The Numeric Rating Scale (NRS), often known as the Numerical Scale, has a score range of 0 to 10 and is the instrument used in this study. To establish the impact of each variable, the analysis uses preliminary tests, including the Kolmogorov-Smirnov Normality Test (p>0.05), the Levene Test homogeneity test (p>0, 05), and the paired t-test. Results The study's findings indicate that: (1) adopting Swedish massage and deep tissue massage for treating overuse injuries has a substantial impact; and (2) implementing Swedish massage and deep tissue massage for treating overuse injuries differs significantly. Conclusions We can draw the conclusion that Swedish massage is better suited for athletes before and during competition, whereas deep tissue massage can be administered following competition. Цель Определить влияние шведского массажа и массажа глубоких тканей на заживление доминирующих мышц у стрельцов. Хотя воздействие массажа нельзя полностью изолировать от травмы, массаж часто снижает работоспособность спортсмена. Материалы и методы В такого рода исследованиях используется количественный эксперимент с двумя группами предварительного и послетестового тестирования. В целенаправленной выборке приняли участие 20 человек, все мужчины-спортсмены-стрельцы из лука в возрасте от 15 до 20 лет. Мероприятие проходило в течение четырех встреч, при этом группы были разделены по порядку пар. Числовая рейтинговая шкала (NRS), часто известная как числовая шкала, имеет диапазон баллов от 0 до 10 и является инструментом, используемым в этом исследовании. Чтобы установить влияние каждой переменной, в анализе используются предварительные тесты, в том числе тест нормальности Колмогорова-Смирнова (p>0,05), тест однородности теста Левена (p>0,05) и парный t-критерий. Полученные результаты Результаты исследования показывают, что: (1) применение шведского массажа и глубокого массажа тканей для лечения травм, вызванных чрезмерным перенапряжением, имеет значительный эффект; и (2) применение шведского массажа и массажа глубоких тканей для лечения травм от переутомления существенно различается. Выводы Можно сделать вывод, что шведский массаж лучше подходит спортсменам до и во время соревнований, тогда как глубокий массаж тканей можно проводить после соревнований. Мета Визначити вплив шведського масажу та масажу глибоких тканин на загоєння домінуючих м’язів у стрільців з лука. Хоча вплив масажу неможливо повністю відокремити від травми, масаж часто знижує результативність спортсмена. Матеріали та методи У цьому виді дослідження використовується кількісний експеримент із двогруповою схемою претест-посттест. У цілеспрямованому відборі було 20 учасників, усі спортсмени-чоловіки, які стрільбали з лука, віком від 15 до 20 років. Діяльність проходила протягом чотирьох зустрічей, групи розділені за порядковим паруванням. Числова рейтингова шкала (NRS), часто відома як Числова шкала, має діапазон балів від 0 до 10 і є інструментом, який використовується в цьому дослідженні. Щоб визначити вплив кожної змінної, в аналізі використовуються попередні тести, включаючи тест нормальності Колмогорова-Смірнова (p>0,05), тест однорідності тесту Левена (p>0, 05) і парний t-тест. Результати Результати дослідження вказують на те, що: (1) застосування шведського масажу та глибокого масажу тканин для лікування травм від надмірного навантаження має значний вплив; і (2) застосування шведського масажу та глибокого масажу тканин для лікування травм від надмірного навантаження суттєво відрізняється. Висновки Можна зробити висновок, що шведський масаж краще підходить для спортсменів до і під час змагань, тоді як глибокий масаж тканин можна проводити після змагань.